2019
DOI: 10.1002/alr.22353
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of surgeons’ ergonomic dynamics with a structured light system during endoscopic surgery

Abstract: Background:The purpose of this study was to use motion capture to collect body posture information during simulated endoscopic sinus surgery interventions performed by both specialists and residents in standing and si ing positions and to analyze that information with the validated Rapid Upper Limb Assessment (RULA) tool, which allows calculation of a risk index of musculoskeletal overload. Methods:Bilateral endoscopic sinus surgery was performed in 5 cadaver heads by 2 residents, and 4 practicing rhinologists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 15 publications
0
28
0
2
Order By: Relevance
“…In order to obtain more detailed and objective information, Vignais et al [ 16 , 17 ] suggested using the scoring system on inertial motion capture (IMC) data, which can be used in real work environments. IMC systems, such as MVN Link by Xsens (Enschede, The Netherlands), have been developed further recently and are now considered as accurate and reliable, especially for the investigation of slower movements [ 18 , 19 ], such as those found during dental treatment procedures [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain more detailed and objective information, Vignais et al [ 16 , 17 ] suggested using the scoring system on inertial motion capture (IMC) data, which can be used in real work environments. IMC systems, such as MVN Link by Xsens (Enschede, The Netherlands), have been developed further recently and are now considered as accurate and reliable, especially for the investigation of slower movements [ 18 , 19 ], such as those found during dental treatment procedures [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the focus of research in this field has concentrated on ergonomic activities and processes within individual medical specialties such as surgery [21,22] or gastroenterology [23]. In particular, during new surgical procedures [24] and new treatment techniques [25][26][27][28], musculoskeletal imbalances have been reported: 66-94% of surgeons report work-related MSD in open surgery [11,21,24,[29][30][31], 73-100% in conventional laparoscopy [32,33], 54-87% in vaginal surgery and 23-80% in robotic surgery [25,27,28,[34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…However, data on static postures are lacking. In previous studies the Rapid Upper Limb Assessment (RULA) [15,16] was used to measure static postures [15]. Static postures can also be analyzed by means of kinematic analysis, for which the computer-assisted acquisition and long-term analysis of musculoskeletal loads system (CUELA) can be used [2,13,[17][18][19].…”
mentioning
confidence: 99%